Sindrom Operasi Punggung Gagal - Fikri Muhammad Rifai Patongai (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background; failed back surgery syndrome is low back pain that has no known cause even though it has been intervened or appears after a surgical intervention aimed at relieving pain in the same location. The aim of this study is that the authors want to present the knowledge about this disease and compare the efficacy between therapies with the Traditional Review method regarding failed back surgery syndrome and its treatment. Result; Strong evidence from large randomized trials shows the superiority of spinal cord stimulation over conservative management and repeated surgery for back surgery syndrome failed to show better neuromodulation than conventional therapy. Conclusion; neuromodulation therapy modalities showed more satisfactory results than other therapies